Endoscopic Orientation of Juxta-pituitary Carotid in Transsphenoidal Approaches: Critical Considerations for Clinical Applications - Ismail, Mostafa; Darwish, Mohab; Tahan, Abd El Rahman El; Herzallah, Islam R. (International Archives of Otorhinolaryngology, 2023)
Introduction In sphenoid sinuses with ill-defined carotid bony landmarks, accidental injury of the internal carotid artery (ICA) remains one of the most challenging complications, which is particularly reported in the endoscopic endonasal transsphenoidal approaches (EETAs).Objectives To describe an anatomical model for the endoscopic orientation of the juxta-pituitary segment of the ICA in relation to the lateral opticocarotid recess (OCR) as a nearby bony landmark.Methods Dissection was performed progressively, simulating the EETA, in twenty fresh adult cadavers. After reducing the posterior and lateral walls of the sphenoid sinuses, various measurements were taken from both lateral OCRs to “contact points” on the juxta-pituitary segment of the ICA and lateral margins of the pituitary gland.Results The current results have enabled us to divide the region between the lateral OCRs into 3 compartments: 2 lateral parasellar compartments contain juxta-pituitary segments of the ICA with a mean width of 8 mm and a narrow range from 7 mm to 10 mm; and a central intercarotid sellar compartment represents the safe region for bone drilling, showing widely variable widths ranging from 9 mm to 20mm. In all specimens, the variation in the width of the intercarotid compartment correlated with the distance between both lateral OCRs.Conclusion The present study improves surgeon awareness of the variations in the course of the ICA through the EETA along sphenoid sinuses with ill-defined bony landmarks. An appreciation of the measurements taken in the present study can help in operative training, and can also provide a base for future studies to confirm ICA courses associated with a higher risk of injury.
Keywords: cadaveric study; internal carotid artery; lateral opticocarotid recess; pituitary gland; transsphenoidal approach